Penerapan Model PBL pada Pembelajaran Bahasa Indonesia Materi Teks Prosedur Kelas V untuk Meningkatkan Keaktifan Siswa - Hamida, Khoirul; Saputra, Henry Januar; Handayani, Retno Suci (PGSD Universitas Muria Kudus, 2024)
The purpose of this research is to analyze Indonesian language learning for class V procedural text material using Problem Basic Learning (PBL) to increase student activity.The research method used was Classroom Action Research (PTK).The research was carried out in two cycles where each cycle consisted of planning, implementing actions, observing and reflecting. The research was conducted on class V students at SD Negeri Bendungan Semarang, totaling 26 students. In this research, data analysis uses qualitative data and quantitative data which is analyzed using descriptive techniques.The results of the research showed that there was an increase in the average results of students' classical learning activities carried out from pre-cycle actions to cycle I and cycle II. The average percentage of student learning activities in the pre-cycle was 49.15% in the